Pemahaman Bahasa Indonesia Di Bidang Pariwisata - Samual Sopian Sagala (Student Scientific Creativity Journal, 2023)
Tourism sector has a good prospect in the future, because it can give big foreign exchange for developing tourism sector. Developing tourism sector needs several factors of human resources, one of them is the communications factors in which language as a means of verbal communication plays an important role. The functions of language and such ast o develop science and technology. And to communicate with other country. The people who are involved in the tourism industry are required to communicate with the tourists in their language. The language which is often used to communicate with the foreign tourist is English. If they cannot understand the English language, the foreign tourist will often find difficulties in communication. The problem are : What are the roles of English tourism in Tobelo? The hypothesis is that the role of the English language and the ability of a person in using the English language is important in the tourism industry.